Single-cell RNA landscape of osteoimmune microenvironment in osteoporotic vertebral compression fracture and Kümmell's disease - Xu, Yude; Huang, Suixiang; Li, Zhencong; Dai, Libing; Wu, Hao; Wang, Peigeng; Yao, Xiguan; Luo, Wei; Liu, Yiming; Yang, Weichao; Feng, Yi; Miao, Haixiong; et al. (Frontiers in Cell and Developmental Biology, 2023)
Background: Single-cell RNA sequencing (scRNA-seq) enables specific analysis of cell populations at single-cell resolution, however, there is still a lack of single-cell level studies to characterize the dynamic and complex interactions between osteoporotic vertebral compression fractures (OVCF) and Kümmell's disease (KD) in the osteoimmunology microenvironment. In this study, we used scRNA-seq analysis to investigate the osteoimmunology microenvironment and cellular composition in OVCF and KD.Methods: ScRNA-seq was used to perform analysis of fractured vertebral bone tissues from one OVCF and one KD patient, and a total of 8741 single cells were captured for single-cell transcriptomic analysis.The cellularity of human vertebral bone tissue was further analyzed using uniform manifold approximation and projection(UMAP). Pseudo-Time analysis and gene enrichment analysis revealed the biological function of cell fate and its counterparts. CellPhone DB was used to identify the interactions between bone cells and immune cells in the osteoimmunology microenvironment of human vertebral bone tissue and their potential functions.Results: A cellular profile of the osteoimmunology microenvironment of human vertebral bone tissue was established, including mesenchymal stem cells (MSCs), pericytes, myofibroblasts, fibroblasts, chondrocytes, endothelial cells (ECs), granulocytes, monocytes, T cells, B cells, plasma cells, mast cells, and early erythrocytes. MSCs play an immunoregulatory function and mediate osteogenic differentiation and cell proliferation. The differentiation trajectory of osteoclasts in human vertebral bone tissue was also revealed. In addition, endothelial cells actively participate in inflammatory infiltration and coupling with bone cells. T and B cells actively participate in regulating bone homeostasis. Finally, by identifying the interaction of ligand-receptor pairs, we found that immune cells and osteoclasts have bidirectional regulatory characteristics, have the effects of regulating bone resorption by osteoclasts and promoting bone formation, and are essential for bone homeostasis..Conclusion:Our analysis reveals a differential landscape of molecular pathways, population composition, and cell-cell interactions during OVCF development into KD. OVCF has a greater capacity for osteogenic differentiation, thanks to its abundance of MSCs and immune cells. However, KD leads to greater bone resorption than bone formation due to depletion of MSCs and a relatively depressed state of the immune system, ultimately causing avascular necrosis of the vertebral body.